Open Journal System in the Era of Paperless Papers - Malik, Tayyaba Gul (Pakistan Journal of Ophthalmology, 2020)
With the start of 2020, we have entered a new decade with the never-ending challenges of the developing world. One of the challenges is the barrier against access to the latest scientific knowledge. To cope with this barrier it is indispensable that the current scientific literature should be made freely available to the resource-constrained countries like Pakistan. Pakistan Journal of Ophthalmology has taken a step forward and joined the club of open access journals through “Open Journal System” (OJS).